Academic Institution Telecommunication Infrastructure Development - Antoniuk, Y.M. (Управляющие системы и машины, 2015)
The problem of the software choice and the hardware solutions, the creation principles and application services of the scientific and educational academic institutions environment in condition of the basic developing, the information communication technology innovation and general globalization is scrutinized. Based on the technological standards analysis that apply to the telecommunications infrastructure and network management centers, the recommendations for the network control center creation, in particular, the basic computer telecommunication center are described.